2022
DOI: 10.1101/2022.03.07.483296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid phenotypic differentiation and local adaptation in Japanese knotweed s.l. (Reynoutria japonicaandR. ×bohemica, Polygonaceae) invading novel habitats

Abstract: PREMISE: Many plant invaders like the Japanese knotweeds are thought to colonize new habitats with low genetic diversity. Such species provide an opportunity to study rapid adaptation to complex environmental conditions. METHODS: Using replicate reciprocal transplants of clones across three habitats, we described patterns of phenotypic response and assessed degree of local adaptation. KEY RESULTS: We found plants from beach habitats had decreased height, number of leaves, leaf area, and biomass allocation to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 136 publications
(208 reference statements)
0
2
0
Order By: Relevance
“…Physiological variation of Japanese knotweed grown in different habitats has been recorded in previous studies, including differences in height, number of leaves, leaf surface area and biomass allocation (Walls, 2010;Yuan et al, 2022). All the rhizomes used for these controlled growth experiments were extracted from the same source, but recent research indicates that the environmental adaptations observed here may be in uenced by the original source of the rhizomes and could have differed if these were collected from another habitat type (Yuan et al, 2022). The growth environment plays a signi cant role in phenotypic presentation, and this study has explored the in uence of speci c environmental variables.…”
Section: Pls Regression Allows Predictions Of Physiological Responsesmentioning
confidence: 87%
See 1 more Smart Citation
“…Physiological variation of Japanese knotweed grown in different habitats has been recorded in previous studies, including differences in height, number of leaves, leaf surface area and biomass allocation (Walls, 2010;Yuan et al, 2022). All the rhizomes used for these controlled growth experiments were extracted from the same source, but recent research indicates that the environmental adaptations observed here may be in uenced by the original source of the rhizomes and could have differed if these were collected from another habitat type (Yuan et al, 2022). The growth environment plays a signi cant role in phenotypic presentation, and this study has explored the in uence of speci c environmental variables.…”
Section: Pls Regression Allows Predictions Of Physiological Responsesmentioning
confidence: 87%
“…Although IAS generally display greater plasticity, this is not always correlated with a tness bene t (Davidson et al, 2011). Physiological variation of Japanese knotweed grown in different habitats has been recorded in previous studies, including differences in height, number of leaves, leaf surface area and biomass allocation (Walls, 2010;Yuan et al, 2022). All the rhizomes used for these controlled growth experiments were extracted from the same source, but recent research indicates that the environmental adaptations observed here may be in uenced by the original source of the rhizomes and could have differed if these were collected from another habitat type (Yuan et al, 2022).…”
Section: Pls Regression Allows Predictions Of Physiological Responsesmentioning
confidence: 94%